A DIMENSÃO CRIATIVA DA DOCÊNCIA: CONCEITUAÇÕES A PARTIR DA PEDAGOGIA RETÓRICA E DA FILOSOFIA DE GILLES DELEUZE - TATIANA DA SILVA RAMOS BATISTA (2022)
This work is linked to the Research Line Educator Formation and Diversity of the Postgraduate Program in Education of the Federal University of Mato Grosso do Sul - Pantanal Campus (PPGE UFMS/CPAN), and to the Research Group Rhetoric and Argumentation in Pedagogy (USP/CNPq). In view of the interest in investigating the relations between thinking, creating, and teaching, the general objective of the research was to elaborate concepts about the creative dimension of teaching. To reach this goal, the following specific goals were elaborated: (i) to reflect on teaching and creation in the interface with the assumptions of rhetorical pedagogy; (ii) to discuss the relations between thought and creation in the scope of Gilles Deleuze's conceptualizations and, also, to identify and discuss the contributions of Deleuze's thought to broaden, or rework, the bases of rhetorical pedagogy; and (iii) to discuss creation in the relation with the teacher's work. The methodology of the research, of qualitative approach, is bibliographical in nature. The methodological path of the research involved the identification of the main concepts mobilized by Deleuzean philosophy regarding the theme of thought as an act of creation, and, equally, the presentation of the main arguments that sustain the paradigm of rhetorical pedagogy. We defend the richness of Deleuzean theoretical contribution to foster debates about thought and creation, contributing, therefore, to reflections about the teaching work, including teaching in the dialogue with the paradigm of rhetorical pedagogy. The results of the research show that teaching is accomplished, to the utmost, through creation: of encounters, of possibilities for participation in rhetorical situations, of aesthetic experiences, of senses and meanings, of imaginative acts and poetic action. We conclude that the creative dimension of teaching is fostered by considering the concepts of: (i) aesthetic experiences and fictions, referring to the centrality of affections, the broadening of sensitivity and the investigation of intensities in teaching, for the creation of fictions, that is, of new worlds; (ii) aesthetics of multiplicity, presenting the need for the teacher to develop taste for the beauty that comes from what is different, from what tenses and makes us think; and (iii) breaking with - and creating - the common, indicating the delicate balance, lived in the act of exercising the creative dimension of teaching, in which teachers think about the possibilities of sharing the common, but also become eager for more aesthetic experiences, moving through the unusual, through what was not perceived, subverting representations.